THE EFFECT OF UREA FERTILIZER LOADED ON HYDROGEL COMPOUNDS PREPARED FROM GELATIN IN INCREASING NITROGEN AVAILABILITY AND REDUCING AMMONIA VOLATILIZATION IN SOIL - Ali Rahim, Benin; J. Sweah, Zainab; Adel Omran, Rashad (Antis-Publisher, 2025)
Objective: This study aims to evaluate the effect of urea fertilizer encapsulated with hydrogel compounds prepared from gelatin on increasing nitrogen availability and reducing ammonia volatilization in soil. Method: A laboratory experiment was conducted using urea fertilizer coated with hydrogel composites at different encapsulation ratios of gelatin to sodium alginate (1:1, 1:2, and 2:1), designated as G1, G2, and G3, respectively. The hydrogels were crosslinked with 7% calcium chloride (CaCl₂) and applied to two soil types, clay loam and sandy loam, at a nitrogen rate of 1000 mg N kg⁻¹ soil. The samples were maintained at field capacity and incubated for 3, 6, 9, 12, 15, 20, and 30 days, during which ammonia volatilization and available nitrogen were measured. Results: The results demonstrated that urea encapsulated with hydrogel compounds significantly reduced ammonia volatilization and enhanced nitrogen availability compared to uncoated urea. Among the treatments, the 2:1 ratio (G3) showed superior performance in minimizing nitrogen losses and improving soil nitrogen retention. Novelty: This study introduces an innovative approach to nitrogen management through hydrogel-based encapsulation, highlighting its potential to improve fertilizer efficiency and mitigate environmental impacts associated with ammonia volatilization.